Ingeniería de tejidos óseos: Estudios in vitro e in vivo con matrices híbridas de vidrio bioactivo, quitosano y polivinilalcohol - Coleta, D. J. (2017)
Synthetic three-dimensional scaffolds for application in bone tissue regeneration should present architecture similar to bone extracellular matrix and provide suitable microenvironment for cell adhesion, proliferation and differentiation. The aims of this work were: 1) to make a structural characterization of a three-dimensional hybrid scaffold (MH) formed as a hybrid porous containing chitosan, polivynil alcohol and bioactive glass by SEM (Scanning Electron Microscopy), 2) to study in vitro potential cytotoxicity from the scaffolds assessing cell metabolic activity (MTT assay) and 3) to study in vivo rabbit response to MH implant into 5.1mm femoral injury, using treated and control animals (n=5). Results: SEM showed well defined MH net with open and interconnected pores, homogeneously organized with 64-234 µm range. MH had no cytotoxic effect detected by MTT. No clinical and biochemical (hemogram, total proteins and transaminases) differences were detected among groups. Histological studies showed a bi-layer tissue at matrix-interface, inner fibrous and outer bony tissues. The intra-scaffold area presented mineralized surface by cementing laminar-granular deposits, some of them resembling osseous formation with osteocytes-like and lining-like cells. However, inside the matrix, leukocyte hemorrhaged exudate with many macrophages, as well as cells debris were observed. MH can be considered a promising bone tissue biomaterial though longer studies should be carried to determine the macrophages cells fate.